2020
DOI: 10.1523/jneurosci.0816-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Spinal Control of Backward Locomotion

Abstract: Animal locomotion requires changing direction, from forward to backward. Here, we tested the hypothesis that sensorimotor circuits within the spinal cord generate backward locomotion and adjust it to task demands. We collected kinematic and electromyography (EMG) data during forward and backward locomotion at different treadmill speeds before and after complete spinal transection in six adult cats (three males and three females). After spinal transection, five/six cats performed backward locomotion, which requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 87 publications
2
18
0
Order By: Relevance
“…We followed ARRIVE guidelines for animal studies (Percie du Sert et al, 2020). In our effort to reduce the number of animals used in research, we used these cats in other studies to answer different scientific questions (Latash et al, 2020;Harnie et al, 2019Harnie et al, , 2021Merlet et al, 2020Merlet et al, , 2021.…”
Section: Animals and Ethical Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed ARRIVE guidelines for animal studies (Percie du Sert et al, 2020). In our effort to reduce the number of animals used in research, we used these cats in other studies to answer different scientific questions (Latash et al, 2020;Harnie et al, 2019Harnie et al, , 2021Merlet et al, 2020Merlet et al, , 2021.…”
Section: Animals and Ethical Informationmentioning
confidence: 99%
“…We collected kinematic data as described previously (Harnie et al, 2018(Harnie et al, , 2021. Videos of the left and right sides were obtained with two cameras (Basler AcA640-100g) at 60 frames/s with a spatial resolution of 640 by 480 pixels.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…We followed the ARRIVE guidelines for animal studies (Percie du Sert et al, 2020). To reduce the number of animals used in research, we used the cats in other studies to answer different scientific questions (Harnie et al, 2018(Harnie et al, , 2019(Harnie et al, , 2021Merlet et al, 2020Merlet et al, , 2021.…”
Section: Animals and Ethical Informationmentioning
confidence: 99%
“…While the neural mechanisms responsible for the control of forward locomotion have been studied in considerable detail (for review, see Grillner, 1975;Grillner and Zangger, 1979;Orlovsky et al, 1999;Rossignol et al, 2006;Kiehn, 2016), our knowledge about the neural mechanisms generating locomotion in other directions is scarce (Deliagina et al, 2019). Although the comparison of the kinematics of forward walking (FW) and backward walking (BW) in humans and animals has revealed substantial differences (Thorstensson, 1986;Eilam and Shefer, 1992;Ashley-Ross and Lauder, 1997;Vemula et al, 2019), the analysis of the muscle activity patterns revealed similar basic flexor-extensor synergies (Pratt et al, 1996;Jansen et al, 2012;Zelik et al, 2014;Harnie et al, 2021). It has been suggested that there are some common direction-independent neuronal networks contributing to the generation of both FW and BW.…”
Section: Introductionmentioning
confidence: 99%